Histopathological characterization of corrosion product associated adverse local tissue reaction in hip implants: a study of 285 cases. Issue 1 (December 2016) - Ricciardi, Benjamin; Nocon, Allina; Jerabek, Seth; Wilner, Gabrielle; Kaplowitz, Elianna; Goldring, Steven; Purdue, P.; Perino, Giorgio
Abstract Background Adverse local tissue reaction (ALTR), characterized by a heterogeneous cellular inflammatory infiltrate and the presence of corrosion products in the periprosthetic soft tissues, has been recognized as a mechanism of failure in total hip replacement (THA). Different histological subtypes may have unique needs for longitudinal clinical follow-up and complication rates after revision arthroplasty. The purpose of this study was to describe the histological patterns observed in the periprosthetic tissue of failed THA in three different implant classes due to ALTR and their association with clinical features of implant failure. Methods Consecutive patients presenting with ALTR from three major hip implant classes (N  = 285 cases) were identified from our prospective Osteolysis Tissue Database and Repository. Clinical characteristics including age, sex, BMI, length of implantation, and serum metal ion levels were recorded. Retrieved synovial tissue morphology was graded using light microscopy. Clinical characteristics and features of synovial tissue analysis were compared between the three implant classes. Histological patterns of ALTR identified from our observations and the literature were used to classify each case. The association between implant class and histological patterns was compared. Results Our histological analysis demonstrates that ALTR encompasses three main histological patterns: 1) macrophage predominant, 2) mixed lymphocytic and macrophagic with or without features of associated with hypersensitivity/allergy or response to particle toxicity (eosinophils/mast cells and/or lymphocytic germinal centers), and 3) predominant sarcoid-like granulomas. Implant classification was associated with histological pattern of failure, and the macrophagic predominant pattern was more common in implants with metal-on-metal bearing surfaces (MoM HRA and MoM LHTHA groups). Duration of implantation and composition of periprosthetic cellular infiltrates was significantly different amongst the three implant types examined suggesting that histopathological features of ALTR may explain the variability of clinical implant performance in these cases. Conclusions ALTR encompasses a diverse range of histological patterns, which are reflective of both the implant configuration independent of manufacturer and clinical features such as duration of implantation. The macrophagic predominant pattern and its mechanism of implant failure represent an important subgroup of ALTR which could become more prominent with increased length of implantation.